Household structure and child outocmes: School enrolment and labour force participation of fostered children in Ghana - Asuman, D.; Boakye-Yiadom, L.; Owoo, N.S. (University of Ghana, 2015)
Children are an integral part of cultural and economic setting of households in Ghana. As such, their welfare outcomes are of a primary concern to the household and the development aspirations of the nation. Child fostering, the practice by which children reside in households where neither parent is present is pervasive in most societies of West Africa. Data from the sixth round of the Ghana Living Standard Survey suggest that approximately 14% of individuals less than sixteen years old reside in households where neither parent is present. The practice of fostering also has important implications for economic studies that have attempted to establish the determinants of child welfare outcomes in societies where the prevalence of fostering is high. This study examines the relationship between household structure and child outcomes by assessing the determinants of school enrolment and labour force participation of primary school age fostered children in Ghana. The study further examines the role of the biological relationship between a child and the caregiver and the school enrolment and market production decisions concerning fostered children. Applying the bivariate probit model to the sixth round of the Ghana Living Standards Survey, the study finds that the personal characteristics of the fostered child (age, gender and relationship to the head of household) are significant determinants of welfare outcomes of fostered children. Characteristics of the head of household particularly the educational attainment of the household head is a strong predictor of the school and labour market outcomes of fostered children. Household demographic characteristics do not exhibit significant influences of the household decisions concerning fostered children; whilst an index of household income suggests that improvements in household income leads to better child outcomes. A key policy recommendation that arises from this study is the need for public programmes and policies that are targeted at improving the welfare outcomes of children taking into account the high mobility of children between households in Ghana
School of social sciences colloquium
Keywords: economic setting; Living Standards; Household; West Africa